STUDI PELAKSANAAN PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT III DI BADAN PENDIDIKAN DAN PELATIHAN PROVINSI JAWA TENGAH - Herbowo, Adrianus Satrio; Yuniningsih, Tri; Mustam, Mohammad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
In the apparatus of state development efforts can not be separated from the role of education and training. Education and training are well supported by the provision of education and training well too. A good curriculum, good teachers, good infrastructure, and good regulations will support the implementation of the optimal education and trainingThe research is descriptive qualitative, so it uses the phenomenon in which there are interview subjects. This phenomenon is about leadership training that consist of referenced curriculum, facilities and infrastructure, lecturer, participant education and training. Where this phenomenon is a decisive indicator and constraining factors of education.Based on the interview can be seen that providing education and leadership training level III which has become routine was still save some fundamental issues that should have the attention of the organizers of the Education and Training Institute of Central Java Province.